2011
DOI: 10.1177/0898264311410693
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Physical Activity in a Sample of Brazilian Older Adults

Abstract: The results indicate that increases in the levels of physical activity can contribute to improvements in quality of life of older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 38 publications
1
31
1
9
Order By: Relevance
“…Contrary to our findings, a recent Brazilian study with older adults reported no major impact of education on autonomy [95]. Our findings seem also at odds with data showing that individuals, including older persons, with high educational attainment experience greater QoL than those with lower educational attainment.…”
Section: Qol Demographics/socio-economics and Life-stylecontrasting
confidence: 57%
“…Contrary to our findings, a recent Brazilian study with older adults reported no major impact of education on autonomy [95]. Our findings seem also at odds with data showing that individuals, including older persons, with high educational attainment experience greater QoL than those with lower educational attainment.…”
Section: Qol Demographics/socio-economics and Life-stylecontrasting
confidence: 57%
“…A atividade física tem apresentado impacto positivo na QV, independente da idade, do sexo e do estado de saúde e tipo de atividade física 20,21 . No presente estudo, observou-se que a prática de atividade física teve um impacto positivo na saúde mental e física de mulheres de meia idade, atuando nos principais domínios da vida.…”
Section: Discussionunclassified
“…foram significativamente maiores nas mulheres ativas e muito ativas, quando comparadas às sedentárias de forma semelhante ao que foi observado no presente estudo 21 . Alguns estudos também têm fornecido suporte a esta associação, realçando a importância da prática de atividade física para mulheres mais velhas e de meia idade, melhorando inclusive a autoestima e o conceito que elas têm de si mesmas 22,23 .…”
Section: Discussionunclassified
“…For example, the domains past, present, and future activities, death and dying, intimacy, and sensory ability were only evaluated in three studies, 29,60,62 and the pain domain of QoL was only evaluated in seven studies. 27,33,37,44,47,57,61 Other QoL domains were assessed in several studies (e.g., physical domain).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…In these studies, the International Physical Activity Questionnaire (IPAQ) 2,54,56,58,60,62,63 and Physical Activity Scale for the Elderly (PASE) 35,36,38,46,55 were the most frequently used instruments (24.13 and 17.24%, respectively) for estimating PA participation. Three studies (10.34%) 35,36,50 used a test battery of functional fitness, and two studies (6.89%) 43,48 used functional capacity self-assessment Box 1 Instruments used to assess physical activity and quality of life in the studies included in the review (instruments listed by acronym; see full names in a footnote to the Supplementary Table online) Physical activity -Accelerometer: measures minutes and counts per day in moderate and vigorous physical activity.…”
Section: Evaluation Of Pa and Qolmentioning
confidence: 99%